2018
DOI: 10.5114/pm.2018.74898
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial histopathology results and evaluation of endometrial cancer risk in geriatric women

Abstract: The incidence of premalignant and malignant endometrial disorders increases during the postmenopausal period. In the literature, endometrial disorders are usually discussed in the context of menopausal status. But there are limited data regarding endometrial disorders in geriatric patients. Early diagnosis of endometrial cancers with aggressive behaviour that increases during the geriatric period may allow simpler treatment options and also decrease the treatment-associated morbidity risk.Records of geriatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
(12 reference statements)
0
9
1
Order By: Relevance
“…It was found that, if EIN was detected in a polyp, concurrent malignant endometrial lesions were more likely to occur in postmenopausal or nulliparous women. Interestingly, many studies have reported that postmenopausal bleeding is associated with increased risk of neoplasia, 12–15 but neither in the present study nor in the Jacobs et al study 11 did such a relation occur. Jacobs et al 11 did not detect any prognostic factor that was related with malignancy, in the hysterectomy material of 39 polyps with atypical hyperplasia 11 .…”
Section: Discussioncontrasting
confidence: 80%
“…It was found that, if EIN was detected in a polyp, concurrent malignant endometrial lesions were more likely to occur in postmenopausal or nulliparous women. Interestingly, many studies have reported that postmenopausal bleeding is associated with increased risk of neoplasia, 12–15 but neither in the present study nor in the Jacobs et al study 11 did such a relation occur. Jacobs et al 11 did not detect any prognostic factor that was related with malignancy, in the hysterectomy material of 39 polyps with atypical hyperplasia 11 .…”
Section: Discussioncontrasting
confidence: 80%
“…Although vaginal bleeding is the most common symptom, patients may present with leucorrhoea, post-coital bleeding or spotting and pelvic pain, or may even have asymptomatic course. 6 The Postmenopausal bleeding may be a one of the manifestation of organic endometrial pathologies such as endometrial polyp, hyperplasia or carcinoma or may be of included in unexplained category if no obvious pathology is detected. 7,8 The endometrial evaluation method includes various modalities such as transvaginal sonography, hysteroscopy, endometrial biopsy, biopsy by pipelle, dilatation and curettage.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment is often required for premalignant or malignant endometrial diseases and exorbitant treatment can thus be avoided if diagnosed at early stage. 6,9 The most common age group of patients with postmenopausal bleeding was 46-50 year with the range of 41 to 80yrs. The youngest patient was 41 yrs while oldest patient was of 80 year.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 188 patients were included in a study [18]. The most common histopathological results were endometrial polyp, atrophic endometrium, and surface epithelium (26.6, 22.3, and 12.8%, respectively).…”
Section: Discussionmentioning
confidence: 99%